Microbial Community, Fermentation Quality, and in vitro Degradability of Ensiling Caragana With Lactic Acid Bacteria and Rice Bran - You, Jingtao; Zhang, Huan; Zhu, Hongfu; Xue, Yanlin; Cai, Yimin; Zhang, Guijie (Frontiers in Microbiology, 2022)
This study aimed to assess the effects of microbial inoculants and growth stage on fermentation quality, microbial community and in vitro degradability of Caragana silage from different varieties. Caragana intermedia (CI) and Caragana korshinskii (CK) harvested at budding (BU) and blooming (BL) stages were used as raw materials to prepare silage respectively. The silages at each growth stage were treated for ensiling alone (control), with 5% rice bran (RB), a combination of RB with commercial Lactobacillus plantarum (RB+LP), and a combination of RB with a selected strain Lactobacillus plantarum L694 (RB+L694). The results showed that the crude protein (CP) content of CI was higher than that of CK, and delay in harvest resulted in greater CP content in Caragana at BL stage. After 60 days of fermentation, the concentrations of lactic acid (LA) in the RB+L694 treatments were higher than those in control treatments (p < 0.05), while the pH, concentrations of NH3-N, Neutral detergent fiber with addition of α-amylase (aNDF) was lower than those in control treatments (p < 0.05). RB+L694 treatments could decreased Acid detergent fiber (ADF) content except in CIBL. In CK silages, adding RB+L694 could reduce bacterial diversity and richness (p < 0.05). Compared with the control, RB+L694 treatment contained higher Lactobacillus and Enterobacter (p < 0.05). In vitro NDF and DM degradability (IVNDFD and IVDMD) was mostly affected by growth period and additive, RB+l694 treatment had higher IVDMD and lower IVNDFD than other treatments (p < 0.05). Consequently, the varieties, growth stages and additives could influence the fermentation process, while the blooming stage should be selected in both Caragana. Furthermore, the results showed that RB and L. plantarum could exert a positive effect on fermentation quality of Caragana silage by shifting bacterial community composition, RB+L694 treatments outperformed other additives.